Comparison of breathhold, navigator‐triggered, and free‐breathing diffusion‐weighted MRI for focal hepatic lesions. Issue 1 (27th November 2012) - Choi, Ji Soo; Kim, Myeong‐Jin; Chung, Yong Eun; Kim, Kyung Ah; Choi, Jin‐Young; Lim, Joon Seok; Park, Mi‐Suk; Kim, Ki Whang
<x xml:space="preserve">Abstract</x> Purpose To compare the breathhold, navigator‐triggered, and free‐breathing techniques in diffusion‐weighted magnetic resonance imaging (MRI) for the evaluation of focal liver lesions on a 3.0T system. Materials and Methods Fifty‐two patients (36 men, 16 women; mean age, 56.4 years) with focal liver lesions underwent breathhold, navigator‐triggered, and free‐breathing diffusion‐weighted imaging (DWI) of the liver on a 3.0 Tesla (T) system. All sequences were performed with b values of 50 and 800 s/mm2 and identical parameters except for signal averages (two for navigator‐triggered, one for breathhold, and four for free‐breathing) and repetition time (3389 ms for navigator‐triggered, 1500 ms for breathhold, and 4400 ms for free‐breathing). A total of 74 lesions (50 malignant, 24 benign) were evaluated. The signal‐to‐noise ratios (SNR) of the liver and lesions, contrast‐to‐noise ratios (CNR) of each lesion, and ADC values of the liver and lesions were compared for each DWI sequence. The detection sensitivity and characterization accuracy were also compared. Results The SNRs of the liver and lesions were significantly lower for breathhold DWI than for non‐breathhold DWI (navigator‐triggered and free‐breathing DWI) for all b values. The CNRs of the lesions were also significantly lower for breathhold DWI than for non‐breathhold DWI. The ADC values of the liver and focal lesions measured using the three DWI techniques were not significantly different and showed good correlation. For lesion detection and characterization, there were no significant differences between breathhold and non‐breathhold DWI. Conclusion Both breathhold and non‐breathhold DWI are comparable for the detection or characterization of focal liver lesions at 3.0T; however, non‐breathhold DWI provides higher SNR and CNR than breathhold DWI. In addition, although free‐breathing and navigator‐triggered DWI sequences show similar performance for 3.0T liver imaging, free‐breathing DWI is more time efficient than navigator‐triggered DWI. J. Magn. Reson. Imaging 2013;38:109–118. © 2013 Wiley Periodicals, Inc.